Academic pressure and academic procrastination: The mediating role of negative coping strategies - Chuanjia Xue; Zhiwei Helian; Yue Li (PLoS ONE, 2025)
Rooted in the Extended Procrastination-Health Framework, this study employed a survey of 600 Chinese university students to elucidate the mechanistic relationships among academic pressure, coping strategies, and academic procrastination. The findings reveal: (1) Academic pressure was positively associated with the increased academic procrastination (β = 0.470, p < 0.001); (2) Academic pressure was significantly positively associated with increased negative coping styles (β = 0.426, p < 0.001), while the negative coping styles was positively associated with the increased academic procrastination (β = 0.158, p < 0.05). (3) Structural equation modeling confirmed that negative coping strategies partially mediate the academic pressure-procrastination nexus (indirect effect = 0.068, proportionate contribution 12.64%), with the model demonstrating excellent fit indices (χ²/df = 2.89, CFI = 0.93, RMSEA = 0.05). Notably, positive coping strategies exhibited no significant mediating effect. This study validates the theoretical pathway “academic pressure - negative coping - academic procrastination” and underscores the important bridging function of negative coping strategies in translating stress into procrastinatory behavior. The results provide empirically grounded intervention targets for universities to disrupt procrastination cycles through targeted emotional regulation and stress management programs.